197k views
3 votes
Help me answer this question:(

Help me answer this question:(-example-1
User Haniff
by
4.9k points

2 Answers

1 vote

Answer:

The correct answer is first option 2√2

Explanation:

It is given that, g(x) = √(x - 4) and h(x) = 2x - 8

To find g(h(x))

We have g(x) = √(x - 4) and h(x) = 2x - 8

h(x) = 2x - 8

g(h(x)) = √((2x - 8)- 4) = √(2x - 12)

To find the value of g(h(10))

g(h(x)) = √(2x - 12)

g(h(10)) = √(2*10 - 12) =√(20 -12) =√8 = 2√2

Therefore the correct answer is first option 2√2

User Shoki
by
5.5k points
1 vote

Answer: first option.

Explanation:

To solve this problem you must plug the function h(x) into the function g(x):


g(x)=√((2x-8)-4)

Now you must simplify by adding like terms, as following:


g(h(x))=√(2x-12)

Substitute x=10 into the fucntion. Therefore, you obtain the following result:


g(h(10))=√(2(10)-12)


g(h(10))=2√(2)

User StackMonk
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.